Правові основи державного терору проти родин учасників повстанського руху в Західній Україні - Вронська, Т. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
The article is dedicated to the legal grounds for state terror to the family members of the participant of insurgent movement in Western Ukraine.